2023
DOI: 10.5102/rbpp.v12i3.8696
|View full text |Cite
|
Sign up to set email alerts
|

Samisake Program is improving economic capabilities urban poor in Bengkulu City, Indonesia

Abstract: The Samisake program, initiated by the Mayor of Bengkulu, Indonesia to alleviate the poverty of urban communities, is an acronym for "Satu Milyar Satu Kelurahan," which means one billion one village. This research proves that the Samisake program can improve the economy of the urban poor in Bengkulu City, Indonesia. The results are incredible; 70.13% managed to create a new business, only 10.02 % misused the loan for consumptive needs and 19.85 % deliberately did not repay the loan. The results showed that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The Suharto research revealed that government assistance in the form of economic capital bridges potential development efforts, which shows that the Samisake program initiated by the Mayor of Bengkulu, Indonesia, can improve the economy and living standards of the urban with a success percentage of up to 70.13%. 10 However, the development of border areas between countries has a complex doctrine that includes security and economic issues. Portella's research reveals a view that embraces both security and economic issues in the Brazilian context.…”
Section: Introductionmentioning
confidence: 99%
“…The Suharto research revealed that government assistance in the form of economic capital bridges potential development efforts, which shows that the Samisake program initiated by the Mayor of Bengkulu, Indonesia, can improve the economy and living standards of the urban with a success percentage of up to 70.13%. 10 However, the development of border areas between countries has a complex doctrine that includes security and economic issues. Portella's research reveals a view that embraces both security and economic issues in the Brazilian context.…”
Section: Introductionmentioning
confidence: 99%